2005
DOI: 10.1191/0961203305lu2158oa
|View full text |Cite
|
Sign up to set email alerts
|

Polymyositis/dermatomyositis-associated lung disease: analysis of a series of 81 patients

Abstract: The objective of this study was to assess the prevalence, clinical, histological and immunological characteristics, and the long-term outcome of polymyositis- (PM) and dermatomyositis- (DM) associated lung disease, and to define subgroups of lung-associated inflammatory myopathies. This retrospective study included 81 consecutive patients diagnosed with PM/DM. Pulmonary involvement was systematically investigated in relation to clinical symptoms by chest radiography, high resolution computed tomography and pul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
75
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(79 citation statements)
references
References 29 publications
3
75
0
1
Order By: Relevance
“…Interstitial lung disease Epidemiology ILD is a frequent manifestation of dermatomyositis/polymyositis with the prevalence of clinically relevant ILD ranging from 17% to 36% [9,[47][48][49][50][51]. In a prospective series of patients with systematic assessment of lung involvement, the prevalence was estimated to be 65% [9].…”
Section: Direct Pulmonary Involvementmentioning
confidence: 99%
See 1 more Smart Citation
“…Interstitial lung disease Epidemiology ILD is a frequent manifestation of dermatomyositis/polymyositis with the prevalence of clinically relevant ILD ranging from 17% to 36% [9,[47][48][49][50][51]. In a prospective series of patients with systematic assessment of lung involvement, the prevalence was estimated to be 65% [9].…”
Section: Direct Pulmonary Involvementmentioning
confidence: 99%
“…Up to half of patients with IIM-associated ILD may eventually die from respiratory failure [13]. The mortality rate is especially high in acute forms of ILD despite immediate and aggressive treatment [48,58].…”
Section: Direct Pulmonary Involvementmentioning
confidence: 99%
“…Acute respiratory deteriorations of ILD have occasionally been reported in patients with idiopathic inflammatory myopathy [11,19,37], as well as rheumatoid arthritis, systemic lupus erythematosus and systemic sclerosis [2,38], and are usually associated with a poor prognosis. Acute/subacute forms of CTD-associated ILD share the features of acute exacerbations of IPF, a condition also characterised by recent onset of increased dyspnoea, diffuse bilateral ground-glass opacities superimposed on subpleural reticular and honeycombing densities, and worsening gas exchange, in the absence of an identifiable cause other than the pre-existing ILD.…”
mentioning
confidence: 99%
“…Each of these antibodies has been associated with antisynthetase syndrome marked by a high frequency of intestitial lung disease compared with PM-DM without such antibodies (Targoff, 2008). Selva-O'Callaghan et al reported that anti-aaRS negative patients with acute interstitial lung disease and pneumomediastinum had an unfavorable prognosis (Selva-O'Callaghan et al, 2005).…”
Section: Myositis-associated Autoantibodiesmentioning
confidence: 99%
“…It is increasingly recognized as a serious complication and a major cause of death in this disease (Douglas et al, 2001, Fathi et al, 2008, Marie et al, 2002. High-resolution computerized tomography in combination with pulmonary function tests provides sensitive tools to detect early signs of intestitial lung disease (Selva-O'Callaghan et al, 2005). The clinical presentation of interstitial lung disease includes progressive dyspnea on exertion, nonproductive cough, and basilar rales, and a rapidly progressive syndrome (HammanRich) may also occur.…”
Section: Clinical Manifestationsmentioning
confidence: 99%